Assessment of exocrine pancreatic function in children and adolescents with direct and indirect testing - Hopson, Puanani; Smadi, Yamen; Mehta, Vijay; Patel, Samit; Mehta, Devendra; Horvath, Karoly (Frontiers in Pediatrics, 2022)
The exocrine pancreas plays a crucial role in digestion. Understanding of the physiology and regulation of exocrine function provides insight into disease processes and basis of functional testing. Specifically, exocrine pancreatic insufficiency (EPI) can cause maldigestion and thus a proper assessment of exocrine pancreatic function is important. There are indirect and direct methods for evaluating pancreatic function. Indirect methods are varied and include stool, serum, urine, and breath tests. Fecal elastase is a commonly used indirect test today. Direct methods involve stimulated release of pancreatic fluid that is collected from the duodenum and analyzed for enzyme activity. The endoscopic pancreatic function test is the newest method that is better tolerated than the Dreiling tube method. Indirect pancreatic function testing may miss cases of mild or moderate EPI, thus direct testing is preferred. This review provides a comprehensive guide to indirect and direct pancreatic function tests as well as an in-depth look at exocrine pancreatic function including anatomy, physiology, and regulatory mechanisms.